PROBLEMATIKA GURU PPKN DALAM MEMANFAATKAN MEDIA PEMBELAJARAN DIGITAL: (Studi Kasus Pada Pembelajaran PPKn di SMP Negeri 1 Banjar Pandeglang) - Adianti, Rere (Academy of Education Journal, 2023)
This Research aims to find out information related of the stages and processes carried out by teachers in disigning learning media in 1 Junior High School of Banjar Pandeglang Regency. And to see how the teacher apply learning media in the process of implementing learning to pursue civic education along with the obstacles faced by teachers while disigning using learning media in the classroom. The type of research used in this research in descriptive qualitative to describe how the problems faced by civic education teachers in utilizing learning media at Banjar 1 Junior High School, Pandeglang Regency. In this research, the analysis technique uses observation, interview, and documentation techniques to strengthen the research data. Based the result of the study, its shows that civic education teachers hace difficulty in developing learning media and lack understanding of the stages in designing creative and innovative learning media to be utilized in the learning process at school.